Wages, Productivity, and Work Intensity in the Great Depression - Julia Darby; Robert A. Hart (Institute for the Study of Labor (IZA), 2002)
We show that U.S. manufacturing wages during the Great Depression were importantly determined by forces on firms' intensive margins. Short-run changes in work intensity and the longer-term goal of restoring full potential productivity combined to influence real wage growth. By contrast, the external effects of unemployment and replacement rates had much less impact. Empirical work is undertaken against the background of an efficient bargaining model that embraces employment, hours of work and work intensity.
Keywords: N62; J31; J24; 330; wages; productivity; work intensity; Great Depression; Lohn; Arbeitsproduktivität; Arbeitsintensität; Lohnverhandlungstheorie; Konjunktur; Wirtschaftsgeschichte; Schätzung; Vereinigte Staaten